INNV-28. TEMOZOLOMIDE IN RENAL DYSFUNCTION. (9th November 2020) - Garzio, Kayla; McElroy, Kelly; Grossman, Stuart; Holdhoff, Matthias; Ozer, Byram; Yankulina, Olga
Abstract: BACKGROUND: Temozolomide (TMZ) is a cytotoxic DNA alkylating agent. It is the only chemotherapy known to improve survival in patients with high grade astrocytomas. The active alkylating species, methylhydrazine, is not recovered in the urine and thus renal function is not expected to affect clearance of this agent. It has never been formally evaluated in adults with eGFR < 36 mL/min/1.73 m 2, and it is often recommended to administer with caution, dose reduce, or withhold therapy. However, lacking other effective therapies, we have elected to administer TMZ at full dose to these patients. This IRB approved retrospective study was conducted to evaluate the safety of this practice. METHODS: The primary endpoint was to characterize the incidence and severity of thrombocytopenia in patients with renal impairment defined as eGFR < 60 mL/min/1.73 m 2 who received TMZ for the treatment of their high grade gliomas (HGG) or primary CNS lymphoma (PCNSL). Secondary endpoints included incidence and severity of neutropenia, lymphocytopenia, hepatotoxicity, and number of cycles administered. Medical records were reviewed for adult patients with HGG or PCNSL treated with TMZ from October 1, 2016-September 30, 2019. RESULTS: Thirty-four patients met criteria for inclusion. Of the 7 patients with eGFR < 36 mL/min/1.73m 2, 33/34 cycles (97%) were completed successfully without grade 3–4 thrombocytopenia. No patients experienced grade 3–4 neutropenia, and grade 3–4 lymphocytopenia occurred in 5 cycles (15%). One patient required discontinuation of TMZ 7 days prior to completion of radiation due to thrombocytopenia. CONCLUSION: The side effect profile from TMZ administered to patients with eGFR < 36 mL/min/1.73 m 2 appears to be similar to that of patients with normal renal function. This is not an unanticipated finding given what is known about the metabolism of the drug.